Radial versus femoral access in patients with coronary artery bypass surgery: Frequentist and Bayesian meta‐analysis. Issue 2 (14th November 2021) - Nikolakopoulos, Ilias; Vemmou, Evangelia; Xenogiannis, Iosif; Karacsonyi, Judit; Rao, Sunil V.; Romagnoli, Enrico; Tsigkas, Grigorios; Milkas, Anastasios; Velagapudi, Poonam; Alaswad, Khaldoon; Rangan, Bavana V.; Garcia, Santiago; et al.
Abstract: Background: The optimal access site for cardiac catheterization in patients with prior coronary artery bypass surgery (CABG) continues to be debated. Methods: We performed a random effects frequentist and Bayesian meta‐analysis of 4 randomized trials and 18 observational studies, including 60, 192 patients with prior CABG (27, 236 in the radial group; 32, 956 in the femoral group) that underwent cardiac catheterization. Outcomes included (1) access‐site complications, (2) crossover to a different vascular access, (3) procedure time, and (4) contrast volume. Mean differences (MD) and 95% confidence interval (CI) were calculated for continuous outcomes and odds ratios (OR) and 95% CI for binary outcomes. Results: Among randomized trials, crossover (OR: 7.63; 95% CI: 2.04, 28.51; p = 0.003) was higher in the radial group, while access site complications (OR: 0.96; 95% CI: 0.34, 2.87; p = 0.94) and contrast volume (MD: 15.08; 95% CI: −10.19, 40.35; p = 0.24) were similar. Among observational studies, crossover rates were higher (OR: 5.09; 95% CI: 2.43, 10.65; p < 0.001), while access site complication rates (OR: 0.52; 95% CI: 0.30, 0.89; p = 0.02) and contrast volume (MD: −7.52; 95% CI: −13.14, −1.90 ml; p = 0.009) were lower in the radial group. Bayesian analysis suggested that the odds of a difference existing between radial and femoral are small for all endpoints except crossover to another access site. Conclusion: In a frequentist and Bayesian meta‐analysis of patients with prior CABG undergoing coronary catheterization, radial access was associated with lower incidence of vascular access complications and lower contrast volume but also higher crossover rate.